2019
DOI: 10.1001/jamanetworkopen.2019.7591
|View full text |Cite
|
Sign up to set email alerts
|

Public Approval of Exception From Informed Consent in Emergency Clinical Trials

Abstract: Key Points Question How does the public view emergency research conducted with an exception from informed consent (EFIC)? Findings In this systematic review of survey data from 27 emergency clinical trials with responses from 42 448 individuals submitted by EFIC trial organizers to the US Food and Drug Administration, public attitudes regarding EFIC varied: 58.4% approved of EFIC in principle, 68.6% approved of family-member enrollment, 73.0% approved of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…It remains unclear whether patients, proxies, health-care providers, administrators, or a general population should be con sidered to be the community. 63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent.…”
Section: Exception From Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear whether patients, proxies, health-care providers, administrators, or a general population should be con sidered to be the community. 63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent.…”
Section: Exception From Consentmentioning
confidence: 99%
“…68 Acceptance of the exception from informed consent procedure was high and varied by the specifics of the situation. 65,69…”
Section: Exception From Consentmentioning
confidence: 99%
“…The Established Status Epilepticus Treatment Trial (ESETT) enrolled participants without prospectively provided consent and supported the finding that the phrasing of statements is important [35]. This is supported by studies showing acceptability varies when asked about personal or general enrolment using deferred consent [36]. In the ESETT trial, participants were asked if they were "glad that themselves or their family members were included in the study" [35].…”
Section: Attitudes Of Ethnic Minorities Towards Deferred Consentmentioning
confidence: 89%
“…The fact that only three studies reported any data on participant ethnicity brings the validity of the representativeness of this data for the general trauma population into question. A 2019 systematic review of studies employing a community consultation survey on the exception from informed consent (EFIC), relevant for many pre-hospital trauma trials, found that the survey respondents were not an accurate representation of the trial population demographic with African American individuals underrepresented [ 40 ]. This supports the argument for further consideration of ethnicity as an important factor in trial design to ensure the study populations are truly representative of the population which they aim to serve.…”
Section: Discussionmentioning
confidence: 99%